The integral poem in Un par de vueltas por la realidad by Juan Ramírez Ruiz - De la Sota Díaz, Edmundo (2022)
Juan Ramírez Ruiz is the author of the concept of the integral poem. This poetic proposal (published in manifesto format) was considered the birth certificate of the Hora Zero group (in the 70s). In this document, the express idea was that poetry should be written as indicated in this founding manifesto. The article intends to verify the fulfillment of the poetic mandate in the lyrical writing of the author of the manifesto. In this perspective, the analysis of the poem «A couple of turns around reality» (signature poem of the author’s first book) is based on the categories proposed in the pragmatics of Luis Ángel Luján, in the hermeneutics of Terry Eagleton and in the textual rhetoric by Stefano Arduini.